Trepanation illustration France 1800s - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Trepanation illustration France 1800s. Trapanation illustration - Plate 20 6 20 extract 300px
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons